Relationship between soil apparent electrical conductivity and soil nutrient of Jawa series in oil palm plantation - Mohd Husin, Ezrin; Wayayok, Aimrun; Bejo, Siti Khairunniza; Mahadi @ Othman, Muhammad Razif (2015)
Soil nutrient management is one of important key to manage an estate land. Nutrient such as potassium (K) and phosphorus (P) is very important for the oil palm growth that seriously affects to the yield. This study was carried out to determine the available P and exchangeable K contents in oil palm plantation based on ECa parameter measured by the soil sensor. The soil samples were collected in oil palm plantation at three different depths; 0 - 15cm, 15 - 30cm and 30 - 45 cm and the soil ECa was measured by using ECa sensor in the plantation. The study showed that ECa parameter had significant positive correlation to exchangeable K and available P at 0.01 level and shallow ECa is a good indicator to estimate P at the depth of 0 - 15 cm with R2 = 0.425.